Revisiting regional trade agreements and their impact on services trade - Mario Marconini (International Centre for Trade and Sustainable Development (ICTSD), 2009)
This issue paper, titled 'Revisiting Regional Trade Agreements and Their Impact on Services Trade' written by Mr. Mario Marconini, is a contribution to that process. The paper exhaustively reviews services disciplines included in several Free Trade Agreements (FTA). The aim of the paper is to enable stakeholders to understand how rules and commitments regarding trade in services have been introduced in FTAs, and how those policies might impact sustainable development in developing countries. The paper starts by examining the main models used for agreements on services disciplines, namely the approaches deployed by the North American Free Trade Agreements (NAFTA), the WTO General Agreement on Trade in Services (GATS) and the EU in form of the Economic Partnership Agreements (EPAs). Unlike already existing research, this analysis goes beyond a discussion of the different mechanisms for liberalization (i.e. the negative and positive approach) thus introducing new groundbreaking research on services provisions in FTAs. With reference to the 3 models for services disciplines, the paper continues with an in depth analysis of different provisions contained in the services chapters. Among others, the analysis addresses scope and coverage, Non-discrimination, market access, domestic regulation, mutual recognition and cooperation ...
Keywords: 330